2009
DOI: 10.1038/nature07842
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CaMKII in single dendritic spines during long-term potentiation

Abstract: Ca2+ / Calmodulin-dependent kinase II (CaMKII) plays a central role in long-term potentiation (LTP), which underlies some forms of learning and memory. Here we monitored the spatiotemporal dynamics of CaMKII activation in individual dendritic spines during LTP using 2-photon fluorescence lifetime imaging microscopy in combination with 2-photon glutamate uncaging. Induction of LTP and associated spine enlargement in single spines triggered transient (∼ 1 min) CaMKII activation restricted to the stimulated spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
832
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(905 citation statements)
references
References 46 publications
56
832
2
2
Order By: Relevance
“…81 Following tetanic stimulation, CaMKII levels increase in the memory associated CA1 region of the brain and LTP induction stimulates CaMKII activity in single spines. 45,82 Several studies have shown that memory associated LTP is associated with CaMKII activation and phosphorylation. Consistently inhibitors of CaMKII and mutation in the T286 residue blocks specifically the induction of LTP.…”
Section: Rna Regulation Is Central To Long-term Memory Formationmentioning
confidence: 99%
“…81 Following tetanic stimulation, CaMKII levels increase in the memory associated CA1 region of the brain and LTP induction stimulates CaMKII activity in single spines. 45,82 Several studies have shown that memory associated LTP is associated with CaMKII activation and phosphorylation. Consistently inhibitors of CaMKII and mutation in the T286 residue blocks specifically the induction of LTP.…”
Section: Rna Regulation Is Central To Long-term Memory Formationmentioning
confidence: 99%
“…CaMKII is multifunctional and plays important roles in synaptic transmission and plasticity that affect behavior, learning, and memory. At molecular level, it modulates a wide range of cellular processes including calcium (Ca 2+ ) homeostasis, gene transcription, receptor function, and cytoskeletal alterations [1,[4][5][6][7][8][9]. It has been implicated in both neuronal death and survival, and its precise role in brain ischemia remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of AMPA receptor numbers in synapses is a well-established mechanism for the expression of long-term potentiation (LTP) (Malenka and Bear 2004). On the other hand, it has also been found that inducing LTP at a single synapse activates CaMKII within the spine containing the synapse but neither induces LTP at nearby synapses nor raises CaM-KII content in nearby spines (Zhang et al 2008;Lee et al 2009). This is consistent with our previous result that there exists an activation threshold for wave propagation, which in the case of a homogeneous spine distribution is k = h. As we have shown in this paper, spine clustering reduces this threshold.…”
Section: Discussionmentioning
confidence: 99%
“…First, CaMKII is found to be abundant at postsynaptic sites where it can detect changes in the local levels of Ca 2+ entering the synapse following plasticity-inducing stimuli, via binding of CaMKII to Ca 2+ /CaM. Activated CaMKII then phosphorylates substrates responsible for the expression of synaptic plasticity, namely, the number and the conductivity of synaptic AMPA receptors (Fukunaga et al 1995;Mammen et al 1997;Barria et al 1997a;Derkach et al 1999;Lee et al 2009). Second, once activated, CaMKII can transition into a Ca 2+ /CaM-independent, hyper-activated state via the autophosphorylation of neighboring enzymatic subunits (Hanson et al 1994; Rich and Schulman 1998), and thus continue to phosphorylate its substrates even after the plasticity-inducing Ca 2+ signal has ended (Saitoh and Schwartz 1985;Miller and Kenney 1986;Lou et al 1986;Yang and Schulman 1999).…”
Section: Introductionmentioning
confidence: 99%